Mucosal burning: A case report of rare finding in maxillary sinus carcinoma - Shriya Dinesh Temgire; Shrinivas S Garje; Vikram V Khare (Wolters Kluwer Medknow Publications, 2021)
Malignant tumors in the maxillary sinus (MxS) are rare and are usually diagnosed when perforating the sinus walls in the later stages. Asymptomatic growth of the malignancy is facilitated by the presence of large air space in the MxS. The clinical presentation depends on the sinus wall involvement by the tumors. Symptoms of maxillary sinus carcinoma (MxSCa) can resemble dental infection that the affected patients may visit dental clinics for seeking treatment. This report presents a case of MxSCa, which was secondarily infected along with the rare clinical finding and chief complaint being severe mucosal burning. Attention toward these rare symptoms should be considered, as cases have not been reported with symptoms of burning sensation in MxSCa. Advanced imaging modality such as computed tomography for prompt identification of such lesions is discussed. The patient's first diagnosis is mostly in an advanced stage with a poor prognosis.